FORMULASI STRATEGI MAKASSAR NEW PORT DAN PELABUHAN BITUNG SEBAGAI INTERNATIONAL HUB PORT - Debby Duakaju; Abdul Rahman Kadir; Jusni Jusni (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
The port industry in Indonesia is more complex than the foreign port, considering Indonesia as an archipelagic country whose territory is more ocean than land. This study aims to formulate a competitiveness strategy that must be applied by Makassar New Port and Bitung Port to become International Hub Port. The next destination identifies which ports should be prioritized to become the International Hub Port based on the most effective and profitable strategies. This research includes explanatory research in the form of applied research that is descriptive (explanation without any hypothesis) by using qualitative approach with focus of analysis to arrange alternative strategy in changing company environment and alternative strategy. Location or place of research is the head office of PT Pelabuhan Indonesia IV (Persero) based in Makassar City. The data collected includes primary and secondary data. Analytical techniques in this research are analysis of IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary), SWOT analysis (Strengths Weaknesses Opportunities Threats), Boston Consulting Group Analysis, QSPM Analysis, and analytical hierarchy process.The result of the research indicates that the appropriate strategy to be implemented by Makassar port is to maximize the infrastructure and superstructure of the port, to prioritize excellent service, and to adopt information technology and empower human resources. The right strategy for Bitung Port is to become an International Hub Port by implementing strategies in the first quadrant through optimizing its own advantages and government support, and increasing customer value proposition. The result of AHP analysis shows that Bitung Port should be prioritized to become International Hub Port based on analysis of various analytical tools with consideration of various criteria such as port location, pond depth, modern equipment, harbor environment, and tariff.